Online Reviews Significantly Drive TikTok Purchases in Indonesia: Ulasan Online Secara Signifikan Mendorong Pembelian TikTok di Indonesia - Jamilah, Siti; Kusuma, Kumara Adji (Universitas Muhammadiyah Sidoarjo, 2024)
This study examines the influence of content marketing, brand image, and online consumer reviews on purchasing decisions on TikTok Shop. Using a quantitative approach with 96 respondents from Sidoarjo, data were collected via a structured questionnaire and analyzed using multiple linear regression. Results indicate that all three factors positively impact purchasing decisions, with online consumer reviews being the most significant. These findings suggest that enhancing content marketing, building a strong brand image, and encouraging positive reviews are crucial for driving consumer purchases on TikTok Shop. Highlight: Significant Impact: All variables influence TikTok Shop purchases. Dominant Factor: Online reviews most affect purchasing decisions. Quantitative Study: Analysis of 96 respondents from Sidoarjo. Keyword: Content Marketing, Brand Image, Online Reviews, TikTok Shop, Consumer Behavior